A Worker’s Suicide as the Collapse of Masculinity: The Analysis of The Movie "My Father's Wings” - Sidar Çınar (Masculinities and Social Change)
My Father's Wings by Kıvanç Sezer (2016) shows us how loneliness and desperation are experienced, based on a case of a Turkish construction worker. This article analyzes the film My Father's Wings using the film sociology methodology and focusing on gender and the approach of the Turkish cinema industry that has emphasized emotions after the 2000s. The intertwined experiences of masculinity crisis and being a worker are discussed by articulating Turkish cinema and Turkey's social and political dynamics in the analysis of the film. Based on the film, the collapse of the two pillars on which masculinity is built as the head of the family and the master worker and individualization in the working class and society in general are discussed within the political and social atmosphere that resulted in everyone's withdrawal to their own world.